Real And Monetary Convergence Of ASEAN-5 Plus Three - Ong, Hway Boon (2006)

(untitled)
Asia consists of numerous countries that vary in population, culture, land area and economic resources. However, within the disparity and diversity of the Asian economies, there are some common grounds that have sparked off regional co-operation. The purpose of this thesis is to evaluate the level of economic convergence of the combinations of ASEAN-5 (namely, Indonesia, Malaysia, the Philippines, Singapore and Thailand), Japan, China and Korea economies, a fundamental source of regional co-operation. The empirical findings suggest that GDP, CPI and interest rates of ASEAN-5, Japan, China and Korea are all cointegrated, signifying synchronisation and initial convergence within the region, a positive indication for closer economic co-operation with lesser adverse impact on any individual economy. Subsequently, three possible economic alliances are identified as ASEAN-5, ASEAN-5, Japan, China and Korea, as well as ASEAN-5, Japan and China. The tests on dynamic properties of GDP of ASEAN-5, GDP of ASEAN-5, Japan and China, CPI of ASEAN-5, Japan China and Korea, and interest rates of ASEAN-5, demonstrate significant macroeconomic linkages among these economies, validating a possible economic co-operation. Apparently, managing the interest rates is a policy tool to keep in check the economy’s price level, the CPI. Since managing CPI would be the concern of most economy to contain inflation, the convergence of CPI among ASEAN-5 + 3 through government intervention, is expected. Furthermore, a relatively short impulse response of ASEAN-5’s interest rates implies monetary co-ordination within the region. Since GDP represents overall macroeconomic activities within an economy, it provides a relatively good implication on the readiness of economies to be integrated. Hence, based on these empirical findings, the first phase of a serious economic integration would be ASEAN-5, to be ready in approximately 4 to 5 years’ time. The second phase should include other economies like Japan, China and perhaps in a later stage, to also include Korea. Besides, the time varying analysis validates these suggestions by revealing gradual convergence for all economies under study. Nonetheless, in order to form a union, ASEAN-5 has to revamp its current financial systems as well as to formulate reasonable and workable economic integration guidelines. Setting clear, consistent and simplified trade procedures and regulations, as well as extending mutual trade collaboration are necessary. Moreover, the underlying incentive structure behind the process of integration should also be made known to all ASEAN economies and not be wiped out with some other trade and non-trade barriers. As for newer ASEAN members like Vietnam, Laos, Myanmar and Cambodia, ASEAN-5 could draft special preferential trade guidelines to boost trade among ASEAN members in preparation to include all ASEAN members into AFTA. However, the realisation of a serious integration may take longer than expected due to the lack of political commitment, economic stability, unpredictable natural disasters and its aftermath, as well as the inevitable spread of deadly diseases.